LACUNA AS A LINGUISTIC UNIT AND ITS INTERPRETATION IN DIFFERENT LANGUAGES (Universal International Scientific Journal, 2026)
This article considers the concept of lacuna (in linguistics, “gap”) as a linguisticunit and analyzes its interpretation in different languages. Lacuna is a unit that represents semantic,pragmatic or culturological components that exist in a particular language or culture, but do not have acomplete equivalent in other languages or cultures. The article considers the classification of lacuna(lexical, grammatical, pragmatic, culturological and stylistic lacunas), methods of identification(contrast analysis, corpus research, translation practice), and intra- and interlingual manifestations oflacuna
Keywords: lacuna; linguistic unit; lexical lacuna